ORGANIZATION OF THE REGIONAL RESEARCH CABINET OF MEDICAL CONTROL IN WESTERN SIBERIA AND ITS ACTIVITY IN THE 1930TH - T. V. Sarycheva (Бюллетень сибирской медицины, 2015)
In this article some brief information about medical control organization and industrial gymnastics in the country and WesternSiberiain the thirtieth is given. The role of the Regional Research cabinet of medi-cal control in this process is characterized. The work of medical and PC institutions is regarded